Kahneman and Tversky and the Origin of Behavioral Economics - Floris Heukelom (Tinbergen Institute, 2007)
Kahneman and Tversky and their behavioral economics stand in a long tradition of applying mathematics to human behavior. In the seventeenth century, attempts to describe rational behavior in mathematical terms run into problems with the formulation of the St. Petersburg paradox. Bernoulli's celebrated solution to use utility instead of money marks the beginning of expected utility theory (EUT). Bernoulli's work is taken up by psychophysics which in turn plays an important role in the making of modern economics. In the 1940s von Neumann and Morgenstern throw away Bernoulli and psychophysics, and redefine utility in monetary terms. Relying on this utility definition and on von Neumann and Morgenstern's axiomatic constraints of the individual's preferences, Friedman and Savage attempt to continue Bernoulli's research. After this fails economics and psychology go separate ways. Economics employs Friedman's positive-normative distinction; psychology uses Savage's normative-descriptive distinction. Using psychophysics Kahneman and Tversky broaden the normative-descriptive distinction and argue with increasing strength for a descriptive theory of rational behavior. A prominent part of contemporary behavioral economics is founded upon the export of Tversky and Kahneman's program to economics. Within this research, two different branches of research can be observed. One branch continues Kahneman and Tversky's search for a descriptive theory of rational behavior and extends the normative-descriptive distinction with a prescriptive part. A second branch takes Tversky and Kahneman's work as a falsification of positive economics. It argues that economics should take account of the psychological critique but stick to rigorous mathematical model building and Friedman's positive-normative distinction.
Keywords: A12; B21; D01; 330; Kahneman and Tversky; behavioral economics; expected utility theory; normative economics; Verhaltensökonomik